A companion to Aristotle - Anagnostopoulos, Georgios (Chichester, U.K. ; Malden, MA : Wiley-Blackwell, 2009)
The Blackwell Companion to Aristotle provides in-depth studies of the main themes of Aristotle's thought, from art to zoology.: The most comprehensive single volume survey of the life and work of Aristotle; Comprised of 40 newly commissioned essays from leading experts; Coves the full range of Aristotle's work, from his'theoretical' inquiries into metaphysics, physics, psychology, and biology, to the practical and productive'sciences' such as ethics, politics, rhetoric, and art.
Notes on Contributors; Preface; Abbreviations of Aristotle's Works; Part I: Aristotle's Life and Works; 1: Aristotle's Life; 2: Aristotle's Works and the Development of His Thought; Part II: The Tools of Inquiry; 3: Deductive Logic; 4: Aristotle's Theory of Demonstration; 5: Empiricism and the First Principles of Aristotelian Science; 6: Aristotle on Signification and Truth; 7: Aristotle's Methods; Part III: Theoretical Knowledge; A. Metaphysics; B. Physics; C. Psychology; D. Biology; Part IV: Practical Knowledge; A. Ethics; B. Politics; Part V: Productive Knowledge; A. Rhetoric.
Includes bibliographical references and index.
Print version record.
Keywords: Aristotle; Aristoteles; Aristotle; Aristoteles, -- v384-v322.; PHILOSOPHY -- History & Surveys -- Ancient & Classical; Philosophie; Electronic books